2020
DOI: 10.1016/j.ajodo.2020.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Precautions and recommendations for orthodontic settings during the COVID-19 outbreak: A review

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) is a contagious disease caused by severe acute respiratory syndrome coronavirus (SARS-CoV-2). It emerged as a global pandemic in early 2020, affecting more than 200 countries and territories. The infection is highly contagious, with disease transmission reported from asymptomatic carriers, including children. It spreads through person-to-person contact via aerosol and droplets. The practice of social distancing-maintaining a distance of 1-2 m or 6 ft-between pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
1
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(124 citation statements)
references
References 58 publications
0
102
1
21
Order By: Relevance
“…There are concerns regarding the appearance, epidemiology, risks and precautions during the disease crisis (Turkistani, 2020) and implications of coronavirus infection for orthodontic treatment (Sunjay Suri et al, 2020). Preventive strategies for infection control (Guo et al, 2020) and aerosol reduction (Maspero et al, 2020) have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are concerns regarding the appearance, epidemiology, risks and precautions during the disease crisis (Turkistani, 2020) and implications of coronavirus infection for orthodontic treatment (Sunjay Suri et al, 2020). Preventive strategies for infection control (Guo et al, 2020) and aerosol reduction (Maspero et al, 2020) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the pandemic caused by the coronavirus, dental professionals must be aware of the occupational risks caused by COVID-19, and stay up to date on infection control guidelines. It is the orthodontist's responsibility to ensure the safety of his/her team and prevent cross-contamination within the dental office (Sunjay Suri et al, 2020;Turkistani, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It may possibly be found on scrubs, nose, and chest of doctors and even contaminate the waterline. 2 Common guidelines issued by regional health regulatory bodies for orthodontic treatment during the pandemic 1,2 :…”
Section: Aerosol-generating Procedures Like Prophylaxis Withmentioning
confidence: 99%
“…[29] Simple procedures such as bonding/debonding and bracket repositioning carry risks of producing aerosols. [30] As the infection and death rates have decreased, some clinics have reopened for routine care at reduced capacities with new protocols. It is essential that all the practitioners should adapt their practices with new recommendations to protect themselves and patients until a vaccine is developed.…”
Section: Protocols and Guidelinesmentioning
confidence: 99%